Questi scese giustificato a differenza di quello L’analisi narrativa illumina la parabola del fariseo e del pubblicano (Luca 18,9-14) - Blajer, Piotr (The Biblical Annals, 2021)
The parable of the Pharisee and the tax collector (Luke 18:9-14) contains an enigmatic expression παρ’ ἐκεῖνον (v.14) which conveys the final judgment on the characters. It is not entirely clear whether it should be interpreted in a comparative or exclusive sense. The present study aims to examine the way the narrator presents the two characters of the parable, the Pharisee and the tax collector, as well as the content of their prayers. Narrative criticism suggests that although both interpretations (comparative and exclusive) are possible it might be better to construe παρ’ ἐκεῖνον with a distinctive value. In fact, the new condition of the tax collector is different from his previous one and clearly distinguishes him from the condition of the Pharisee. In other words, the application of the narrative method suggests to translate the enigmatic complement παρ’ ἐκεῖνον in such a way that it makes visible the difference existing between the two characters.